Rho, a Fraction From Rhodiola crenulate, Ameliorates Hepatic Steatosis in Mice Models - Yi, Qin; Sun, Puyang; Li, Juan; Kong, Siming; Tian, Jinying; Li, Xuechen; Yang, Yanan; Zhang, Peicheng; Liu, Yuying; Han, Jingyan; Zhang, Xiaolin; Ye, Fei (Frontiers in Physiology, 2018)
The prevalence of nonalcoholic fatty liver disease (NAFLD), which is developed from hepatic steatosis, is increasing worldwide. However, no specific drugs for NAFLD have been approved yet. The aim of this study was to evaluate the effects of Rho, a fraction from Rhodiola crenulate, on nonalcoholic hepatic steatosis. Three mouse models with characteristics of NAFLD were used including high-fat diet (HFD) induced DIO mice, KKAy mice, and HFD combined with tetracycline stimulated Model-T mice. Hepatic lipid accumulation was determined via histopathological analysis and/or hepatic TG determination. The insulin sensitivity was evaluated by insulin tolerance test (ITT), glucose tolerance test (GTT) and hyperinsulinemic-euglycemic clamp, respectively. The pathways involved in hepatic lipid metabolism were observed via western-blot. Furthermore, the liver microcirculation was observed by inverted microscopy. The HPLC analysis indicated that the main components of Rho were flavan polymers. The results of histopathological analysis showed that Rho could ameliorate hepatic steatosis in DIO, KKAy, and Model-T hepatic steatosis mouse models, respectively. After Rho treatment in DIO mice, insulin resistance was improved with increasing glucose infusion rate (GIR) in hyperinsulinemic-euglycemic clamp, and decreasing areas under the blood glucose-time curve (AUC) in both ITT and GTT; the pathways involved in fatty acid uptake and de novo lipogenesis were both down-regulated, respectively. However, the pathways involved in beta-oxidation and VLDL-export on hepatic steatosis were not changed significantly. The liver microcirculation disturbances were also improved by Rho in DIO mice. These results suggest that Rho is a lead nature product for hepatic steatosis treatment. The major mechanism is related to enhancing insulin sensitivity, suppressing fatty acid uptake and inhibiting de novo lipogenesis in liver.